New pathways in microsimulation - Dekkers, Gijs (Ashgate Publishing Limited, 2014)
Microsimulation as a modelling tool in social sciences has increased in importance over the last few decades. Once restricted to a handful of universities and government departments, as a scientific field it has achieved a new dynamism during the last decade. As computing power increases and data availability becomes more widespread, microsimulation models can be put to hitherto unprecedented uses. Edited by leading experts in the field, this book illustrates recent advances, methodologies and uses of socioeconomic microsimulation in social sciences around the world. It does so by analysing.